TEKS IKLAN KOMERSIAL PARFUM UNTUK PRIA - Dewa Ayu Kadek Claria (Universitas Warmadewa, 2018)
[Title: Text of Commercial Advertisement on Men’s Perfume] This research aims at identifying the text of commercial advertisement on men’s perfume because the text has its own typically, so the text can be distinguished from the other written text. The problem analyzed in this research are how the lexicogrammatical (transitivity, mood, theme) of commercial advertisement on men’s perfume? How the situational context of commercial advertisement on men’s perfume? The theories used in this study consist of theory Linguistic Functional Systemic by Halliday. This research only reaches a few aspect of LSF. Meanwhile some other elements such as expression, logico-semantic and metaphor are not yet reviewed. This study is also limited on commercial advertisement on men’s perfume which is obtained from the printed media. For the next research commercial advertisement on electronic media should be reviewed in the terms of phonology.